Moderate Coffee Consumption and Cardiovascular Health: Literature Review of Benefits, Risks and Individual Variations - Wawan, Achmad Hendra Hartawan (LifeSciFi, 2024)
The study aims to evaluate the relationship between coffee consumption and cardiovascular risk by using literature review approach. The findings reveal that moderate coffee consumption has been associated with various cardiovascular benefits, including reduced mortality and improved metabolic health, particularly among individuals with healthy lifestyles and without pre-existing conditions such as hypertension or metabolic syn-drome. Bioactive compounds in coffee, including caffeine, phenolic acids, and antioxidants, contribute to these benefits by reducing inflammation, enhancing vascular function, and improving insulin sensitivity. However, excessive coffee consumption can have adverse cardiovascular effects, such as elevated blood pressure and increased risk of arrhythmias, especially in individuals with hypertension or genetic predispositions to caffeine sensitivity. Genetic factors, such as variations in the CYP1A2 gene affecting caffeine metabolism, further modulate individual responses to coffee. This highlights the need for personalized recommendations that consider genetics, health status, and consumption patterns to optimize coffee’s cardiovascular benefits. Additionally, understanding the timing of coffee intake in relation to individual metabolic rhythms may further enhance its health-promoting potential.